This preview shows page 1. Sign up to view the full content.
Unformatted text preview: x = s + t 2 y = (x+3) (x2) = x^2  2x + 3x  6 = x^2 +x 6 0 (Zero) Y = 2x^2 + 6x + 4 m= 8 = 2x^2 + 2x + 4x + 4 n= 6 = 2x (x + 1) +4 (x + 1) = (2x + 4) (x+1) = 2 (x + 2) (x+1) therefore the zeros are 2 and 1...
View
Full
Document
This note was uploaded on 02/10/2011 for the course ICE 4M1 taught by Professor Deabr during the Spring '11 term at Spring Arbor University.
 Spring '11
 Deabr

Click to edit the document details